Pengaruh Online Customer Review, Online Customer Rating, Dan Kepercayaan Konsumen Terhadap Keputusan Pembelian Pada Pengguna Shopee di Kabupaten Tabanan (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2026)
Purchasing decisions are the final phase in consumer behavior when individuals choose to buy a product or service after considering various options. This study aims to analyze how online customer reviews, online customer ratings, and consumer confidence influence buying decisions among people who use Shopee in Tabanan Regency. The research population includes all Tabanan Regency residents who shop online through the Shopee application. The study used 120 people as a sample, with a technique for taking non-probability sampling and the method was purposive sampling. Data analysis was carried out using multiple linear regression. The research findings reveal that online customer reviews and consumer trust have a positive and significant influence on buying decisions. Meanwhile, online customer rating shows no influence on buying decisions. Together, online customer reviews, online customer ratings, and consumer trust have a positive and significant influence on purchasing decisions.